A new species of the Meropeidae (Insecta: Mecoptera) from mid-Cretaceous Myanmar amber. (December 2020) - Sun, Haocheng; Gao, Yunpeng; Zhao, Xiangdong; Wang, Bo; Xiao, Chuantao
Abstract: The Meropeidae (earwigflies) is a small family of Mecoptera with only three extant and three fossil species. In this paper, a new species of Meropeidae Burmomerope bashkuevi sp. nov., is described based on an exceptionally well-preserved specimen from mid-Cretaceous Myanmar amber. It can be distinguished from other species mainly by most simplified wing venation, four veins both in radial and medial sectors, massive antenna with wide flagellomeres and very thin and elongated last segments of female abdomen. Our new finding not only represents the fourth species of Mesozoic Meropeidae, but also the third female record of extinct earwigflies, which augments the diversity of Mesozoic earwigflies.